2021
DOI: 10.1038/s41598-021-97477-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the efficacy of sinus irrigation with traditional Caldwell–Luc procedure following odontogenic cyst surgery involving the maxillary sinus

Abstract: A large maxillary odontogenic cyst could intrude into the maxillary sinus. The traditional approach following surgery for such a cyst is the Caldwell–Luc procedure. However, the traditional CDL procedure is associated with more complications and damage of the sinus mucosa. The purpose of this study was to assess a new method with easier operation, which not only prevented postoperative infection but also caused less damage to the maxillary sinus mucosa. A large odontogenic cyst in the maxillary sinus of 40 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…If there is no improvement in symptoms, surgical treatment such as removing the odontogenic cause and irrigation of the maxillary sinus can be selected. After the dental cause is removed, primary closure is performed, and maxillary sinus irrigation is done as sinus irrigation can relieve postoperative reactions, reduce the probability of sinus infection, and protect the function of the maxillary sinus [ 9 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If there is no improvement in symptoms, surgical treatment such as removing the odontogenic cause and irrigation of the maxillary sinus can be selected. After the dental cause is removed, primary closure is performed, and maxillary sinus irrigation is done as sinus irrigation can relieve postoperative reactions, reduce the probability of sinus infection, and protect the function of the maxillary sinus [ 9 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gang et al showed that the chronic maxillary sinusitis was healed within 8–12 weeks of Caldwell–Luc surgery followed by sinus irrigation. None of the patients complained about nasal obstruction or facial paresthesia, and no further major complications were noticed after 36 months of surgery [ 9 ]. In our study, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a pneumatized bone, it consists mainly of a compact lamina. As a waste surgical material, part of the maxillary bone can be obtained during Caldwell-Luc maxillary sinus surgeries [26]. Currently, the development of less invasive endoscopic methods of maxillary sinus surgery, with the special role of functional endoscopic sinus surgery, has caused Caldwell-Luc operations to be performed relatively rarely [27,28].…”
Section: Introductionmentioning
confidence: 99%